Juventude e cultura política: a escola pública e a construção do capital social dos estudantes do ensino médio de Francisco Beltrão - Dartora, Ivania (2019)
Our democratic regime has a recent history and a context of authoritarian periods, resulting in a political system that undergoes constant crises of confidence in relation to its institutions and representatives. Considering that a democracy achieves its legitimacy and consolidation based on values and attitudes, the objective of our research was to analyze how the school, one of the socializing institutions, influences the formation of a participatory or apathetic political culture. The context of political crisis reflects the importance of a study on the perceptions of young students, considering that we seek to respond to concerns about building participatory social capital at school, but also how these students perceive political socialization, participation and the democratic regime. The school is defined here as a formal socializing institution, which fulfills the function of transmitting knowledge, but also informal, by providing social exchanges between the different actors that are part of the school context. For that, we started from the literature review specialized in the studies of political culture, social capital and school, with Almond and Verba, Putnam e, Dubet and Martuccelli, seeking to understand the context in which the research subjects are inserted. Considering that our project was part of the Research Line: Society, Knowledge and Education, of the Postgraduate Program in Education, of the State University of Western Paraná, we delimit the research subjects as being part of the third year of high school , from the Public Education Network, in the municipality of Francisco Beltrão. In addition, as it is a survey based on the survey technique, the questionnaire was applied considering a sample by probabilistic clusters, totaling 174 interviews, which went through the statistical processing of the Statistical Package for Social Science (SPSS) software. With the SPSS we relate the variables used to define the fundamental dimensions of the research. When comparing with other research in the area, the difference of this study is the fact that these young people have participated or followed the School Occupations of 2016, being that we identified that the students participating in the study still have high levels of distrust in political institutions, as well as in representatives and; continue to question the conventional aspects of politics, despite claiming that democracy is the best regime and recognizing the importance of participation